2013
DOI: 10.1021/jp409570f
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics and Dynamics of Dye-Doped Conjugated Polymer Nanoparticles by Time-Resolved and Fluorescence Correlation Spectroscopy

Abstract: Fluorescent dye encapsulated conjugated polymer nanoparticles have been paid significant attention for potential applications in photonics and biophotonics due to their high brightness and better photostability. Bright, photostable, and monodispersed Nile Red (NR) dye encapsulated poly-Nvinylcarbazole (PVK) fluorescent polymer nanoparticles have been prepared to understand the influence of size of particles and the concentration of dye inside the particles on the photophysical properties by using steady-state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…QTH (0.04×10 −6 M ) encapsulated in PMMA NPs were prepared by using a simple solution‐based reprecipitation method described previously (the detailed procedure is given in the Supporting Information) 36. 44, 50 Furthermore, the reprecipitation technique was employed for the fabrication of both QTH and NR encapsulated in PMMA NPs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QTH (0.04×10 −6 M ) encapsulated in PMMA NPs were prepared by using a simple solution‐based reprecipitation method described previously (the detailed procedure is given in the Supporting Information) 36. 44, 50 Furthermore, the reprecipitation technique was employed for the fabrication of both QTH and NR encapsulated in PMMA NPs.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the photophysics and rotational motions of encapsulated dye molecules inside the semiconducting polymer nanoparticles have been discussed 35. The influence of particle size and the concentration of dye inside the particles on the photophysical properties has been investigated by using steady‐state, time‐resolved fluorescence spectroscopy, and fluorescence correlation spectroscopy (FCS) 36. Thus, dye‐doped polymer nanoparticles were recently found to be a suitable candidate for photonic, biophotonic, bioimaging, and sensing devices 29.…”
Section: Introductionmentioning
confidence: 99%
“…The inner environment of PNPs is heterogeneous with different polarities, while silica matrix is commonly homogeneous. The FCS study on Nile red (NR) dye-doped different-sized PVK PNPs using a 532-nm laser source (for the direct excitation of NR dye molecules) is reported [21] and it is found that the hydrodynamic radius is increased from 20 to 55 nm (shown in figure 3C) on increasing the size of the PNPs from 40 to 100 nm. We have calculated the particle concentration of as-prepared aliquots, which is on the order of ∼50-80 nM.…”
Section: Fcs For Particle Brightness With Number Of Dye Molecules Insmentioning
confidence: 99%
“…Pecher and Mecking [19] have described the fundamental photophysics of conjugated PNPs. Furthermore, the colour tunability and brightness of fluorescent PNPs can be enhanced by encapsulating organic fluorophores inside the PNPs [20][21][22]. Photophysics of encapsulated dye molecules in PNPs and the confined motion of dye molecules were reported recently [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Among the important nanostructures that have found use in biology and medicine one can list quantum dots (QDs Nanoparticles have attracted great interest due to their promising potential for applications in biological sciences and other biomedical 1,2 , nanoparticles of gold, silicon, silica, metal oxides and several forms of carbon and the recently advanced semiconducting polymer dots (Pdots). Nanoparticles are used as drug-delivery vehicles, biosensors, imaging tools and markers, where their special chemical and optical properties are employed for analytical and diagnostic purposes 3 . Quantum dots (QDs), especially, found the most wide-spread uses in scientific applications.…”
Section: Introductionmentioning
confidence: 99%